Frequency and Magnitude of Internal Organ Colonization Following Exposure of Laying Hens to Different Oral Doses of Salmonella enteritidis - Gast , Richard K.; Guraya, Rupa; Guard, Jean; Holt, Peter S. (International Journal of Poultry Science, 2011)
Contaminated eggs produced by infected laying hens continue to pose a significant public health concern as a leading source of transmission of Salmonella enteritidis infections to humans. A recently implemented national regulatory program for egg-producing poultry in the United States seeks to control egg-borne transmission of illness to consumers via a diverse program of mandatory risk reduction practices plus testing to detect infected flocks. However, many aspects of S. enteritidis infections in laying hens, including the precise relationship between the magnitude of oral exposure and infection parameters such as the numbers of bacteria that reach internal tissues, remain unresolved. In the present study, groups of laying hens were experimentally infected with oral doses of 104, 106, or 108 CFU of a phage type 13a strain of S. enteritidis and the number of S. enteritidis cells in the livers of infected hens was determined at 5 d and 20 d post-inoculation. The frequency of S. enteritidis recovery from livers ranged from 30% (104 CFU dose) to 90% (108 CFU dose) at 5d post-inoculation and from 0% (104 CFU dose) to 40% (108 CFU dose) at 20 d post-inoculation. Significantly (p<0.05) greater numbers of S. enteritidis were isolated from livers at both 5 d and 20 d post-inoculation following inoculation with 108 CFU than after administration of either of the two lower doses. These results demonstrate that the oral exposure dose significantly affects important parameters of S. enteritidis infection in laying hens and could thereby influence the outcome of testing efforts. Interpreting the potential implications of testing results and improving the effectiveness of testing protocols are both contingent on understanding how different levels of exposure are likely to be detected by particular sampling methods